Konsep Diiri Awal dan Akhir Perawatan Rehabilitas Napza pada Pasien Institusi Penerima Wajib Lapor (IPWL) Rawat Inap - Rian Irana Purwa, Rian Irana (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2020)
The purpose of this study was to determine the differences between the initial and final self concept of treatment for drug rehabilitation in patients with mandatory report recipient institutions (IPWL) at Ernaldi Bahar Hospital, Palembang. and the hypothesis of this study is that there is a difference between the self-concept of beginning and the end of treatment for drug rehabilitation in patients with the Obligatory Report Receiving Institution (IPWL) hospitalized at Ernaldi Bahar Hospital Palembang. The variables of this study are the initial self-concept and final self-concept. The subjects in this study were all drug rehabilitation patients who carried out inpatient rehabilitation at Dr. Ernaldi Bahar Hospital in South Sumatra Province in March - May 2019, which amounted to 40 people, because the number of research subjects did not reach 100 people, so this study took all population numbers which numbered 40 people. The data collection instrument used in this study is the initial self-concept scale and final self-concept scale. In this case it was carried out using a paired t-test, to test differences in samples in paired data. The results showed that there was a difference between the self-concept of the beginning and end of treatment for drug rehabilitation in patients with mandatory report receiving institutions (IPWL) inpatient care at Ernaldi Bahar Hospital Palembang, tcount> ttable: - 9,292> 2,023 or - 9,292> 2,721. = 0.05 and a = 0.01 which means that there is a difference between the initial self-concept and the final self-concept of rehabilitation care.